STRATEGI KOMUNIKASI VISIONET DALAM MEMBANGUN CITRA UNTUK GENERASI MILENIAL - Dewi Sartika Karo-karo; Lina Sinatra Wijaya (Universitas Lambung Mangkurat, 2019)
This study aims to describe the communication strategies carried out by VisioNet. The communication strategy applied, has a positive impact on both company members and prospective employees especially the millennial generations. This is a descriptive qualitative research. For gathering the data, the in depth-interview to the millennials generations is used. The results of this study indicate that VisioNet carried out the communication strategy through various media, such as social media (Instagram, facebook, youtube) and printed media (brochures, bulletins, x-banners, banners). In addition, Internal communication through seminars and general classes is also used to build the internal relations with the employees. VisioNet also carries out an employer brand through website, social media, job fair, newsletter/release, publication, seminar general classes and also some events to build the image of the company among the target audience.